2007
DOI: 10.1038/nm1591
|View full text |Cite
|
Sign up to set email alerts
|

Increased dietary intake of ω-3-polyunsaturated fatty acids reduces pathological retinal angiogenesis

Abstract: Many sight-threatening diseases have two critical phases, vessel loss followed by hypoxia-driven destructive neovascularization. These diseases include retinopathy of prematurity and diabetic retinopathy, leading causes of blindness in childhood and middle age affecting over 4 million people in the United States. We studied the influence of ω-3-and ω-6-polyunsaturated fatty acids (PUFAs) on vascular loss, vascular regrowth after injury, and hypoxia-induced pathological neovascularization in a mouse model of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
576
1
9

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 628 publications
(601 citation statements)
references
References 30 publications
15
576
1
9
Order By: Relevance
“…Together, the present study and our previous report (28) demonstrate a central role of EDPs and EETs in angiogenesis and tumorigenesis, demonstrating that the CYP/sEH pathway plays a critical role in mediating the antiangiogenic and anticancer effects of omega-3 fatty acids (4,9). These findings also illustrate unique opportunities to treat pathological angiogenesis and cancers using omega-3 lipids.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Together, the present study and our previous report (28) demonstrate a central role of EDPs and EETs in angiogenesis and tumorigenesis, demonstrating that the CYP/sEH pathway plays a critical role in mediating the antiangiogenic and anticancer effects of omega-3 fatty acids (4,9). These findings also illustrate unique opportunities to treat pathological angiogenesis and cancers using omega-3 lipids.…”
Section: Discussionsupporting
confidence: 84%
“…These conflicting results can at least partially be explained by our findings of the opposite effects of EETs and EDPs on angiogenesis. Our findings further indicate that sEH could be a potential therapeutic target to treat retinal neovascularization, which is a major cause of blindness in humans (4). DHA is most enriched in retinal tissues, compromising ∼60% of polyunsaturated fatty acids in retina (18).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…17,18 RvD1, which possesses anti-inflammatory and pro-resolving ability in many process of inflammatory resolution, has demonstrated that it can attenuate inflammatory responses in ALI, 10,11 peritonitis, 19,20 kidney ischemia-reperfusion injury, 21 and retinopathy. 22 Here our study was focused on the effects of RvD1 on disruption of pulmonary barrier in ALI and was undertaken to investigate possible molecular and cellular mechanism of RvD1. Our results showed that the effect of 5 mg/kg RvD1 is potent, which is in accordance with the previous experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of resolvin E1 were shown to originate from blocking stimulation of LTB 4 and inhibiting LTB 4 -induced NF-κB activation by binding to the LTB 4 receptor BLT1 [150]. A recent study has put forward supporting evidence that omega-3 fatty acids and their bioactive products significantly reduce pathological angiogenesis, both through reduction of hypoxic stimulus as well as through resolvin-mediated activity [151].…”
Section: Influence Of Dietary Fats On Aa Cascadementioning
confidence: 99%